Novel design of multiplexer and demultiplexer using reversible logic gates - Nath Nune, Veerendra; Purna R, Addanki (International Journal of Engineering and Technology, 2018)
Reversibility is the prominent technology in the recent era. In reversible logic the number output lines are equal to the number of input lines. In reversible logic the inputs are to be retrieved from the outputs. Reversible logic gates are user defined gates. Reversible logic owns its applications in various fields which include low power VLSI. In this paper multiplexer is implemented using QCA, SAM and QCA & SAM gate. Also demultiplexer is implemented using two new reversible logic gates RAMESH and RAMESH-1 gates. These designs are simulated and synthesized using Xilinx ISE 12.1 and Mentor Graphics tool. The result shows that the proposed designs are more efficient in terms of gate count, quantum cost and power consumption.Â Â